2007
DOI: 10.1021/nn700189h
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Au-Fe3O4 Nanoparticles for Protein Separation

Abstract: In this article, we report the synthesis of bifunctional Au-Fe(3)O(4) nanoparticles that are formed by chemical bond linkage. Due to the introduction of Au nanoparticles, the resulting bifunctional Au-Fe(3)O(4) nanoparticles can be easily modified with other functional molecules to realize various nanobiotechnological separations and detections. Here, as an example, we demonstrate that as-prepared Au-Fe(3)O(4) nanoparticles can be modified with nitrilotriacetic acid molecules through Au-S interaction and used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
220
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 371 publications
(223 citation statements)
references
References 35 publications
3
220
0
Order By: Relevance
“…[367] Currently, there have been considerable number of reports on synthesizing magnetic nanoparticles covered by gold through microemulsion, [368] chemical reduction, [369] coprecipitation, seed mediated growth, [370] selfassembly, [371] sonochemical reduction, [372] thermal decomposition, [91] and laser irradiation [373] approaches. Bao et al [374] have also reported synthesis of gold-magnetite composites involving discrete gold nanoparticles on magnetite surface which can be useful for applications such as protein separation, optical imaging, or catalysis, where a full coating is not required. Overlaying of gold can be facilitated by attachment of gold seeds that form a protective layer to increase the particle stability against particle aggregation and make them resistant to chemical attacks.…”
Section: Gold Coatingmentioning
confidence: 99%
“…[367] Currently, there have been considerable number of reports on synthesizing magnetic nanoparticles covered by gold through microemulsion, [368] chemical reduction, [369] coprecipitation, seed mediated growth, [370] selfassembly, [371] sonochemical reduction, [372] thermal decomposition, [91] and laser irradiation [373] approaches. Bao et al [374] have also reported synthesis of gold-magnetite composites involving discrete gold nanoparticles on magnetite surface which can be useful for applications such as protein separation, optical imaging, or catalysis, where a full coating is not required. Overlaying of gold can be facilitated by attachment of gold seeds that form a protective layer to increase the particle stability against particle aggregation and make them resistant to chemical attacks.…”
Section: Gold Coatingmentioning
confidence: 99%
“…The strong magnetism of the plasmonic-magnetic nanohybrids and the CO superior catalytic activity of the Au-Co coreshells were showed as a result of incorporating magnetic heterometals into gold particles. The authors [22] also synthesized bifunctional Au-Fe3O4 nanohybrids through the conjugation of Au particles to thiol-modified Fe3O4 nanoparticles. Lysine contained both amino and carboxylic groups played dual roles as both linker and capping agent in attaching metals on Fe2O3 particles.…”
Section: Synthesis Of Plasmonic-magnetic Hybrid Nanostructuresmentioning
confidence: 99%
“…Magnetic iron oxide nanoparticles (MNPs) have attracted considerable interest due to its superparamagnetism, and offered many exciting opportunities in biology and biomedicine, including magnetic resonance imaging, magnetic hyperthermia therapy, biosensor, separation and purification of protein and cell [1][2][3][4][5]. Meanwhile, the gold NPs have been extensively used in biosensor, surface enhanced Raman spectroscopy, and therapy applications, due to its well-known catalytic activity, optical properties, chemical functionality, and biocompatibility [6][7][8].…”
Section: Introductionmentioning
confidence: 99%